Isolation and Characterization of Plant Growth-Promoting Bacteria from the Rhizosphere of Medicinal and Aromatic Plant Minthostachys verticillata - Meneguzzi, Romina del Valle (2024)
This study aimed to isolate and characterize Pseudomonas native strains from the rhizosphericsoil of Minthostachys verticillata plants to evaluate their potential as plant growth-promotingrhizobacteria (PGPR). A total of 22 bacterial isolates were obtained and subjected to various biochemicaltests, as well as assessments of plant growth-promoting traits such as phosphate solubilization,hydrogen cyanide production, biocontrol properties through antibiosis, and indole acetic production.Genotypic analysis via 16S rRNA gene sequencing and phylogenetic tree construction identified thestrains, with one particular strain named SM 33 showing significant growth-promoting effects onM. verticillata seedlings. This strain, SM 33, showed high similarity to Stutzerimonas stutzeri basedon 16S rRNA gene sequencing and notably increased both shoot fresh weight and root dry weightof the plants. These findings underscore the potential application of native Pseudomonas strains inenhancing plant growth and health, offering promising avenues for sustainable agricultural practices.